Are Invasive Patterns of Non-native Insects Related to Woody Plants Differing Between Europe and China? - Roques, Alain; Shi, Juan; Auger-Rozenberg, Marie-Anne; Ren, Lili; Augustin, Sylvie; Luo, You-qing (Frontiers in Forests and Global Change, 2020)
Forests are increasingly threatened worldwide by the establishment of non-native species arriving from other continents with globalization of trade and international travels. We compiled comprehensive lists of non-native insects associated to woody plants in Europe and China to compare their invasive patterns between these two regions. By 2019, a total of 449 species have colonized forest, ornamental and fruits trees and shrubs in Europe whereas only 77 species were reported in China, a likely underestimated number because studies concentrated on economically-important species. Approximately 6.1 new species have been detected per year since 2000 in Europe vs. only 1.9 in China. Europe and China also exhibited distinct patterns in the invasion sources. Most non-native species recorded in Europe originated from Asia (37.2%), and more especially from China (22.9%) whereas Europe was only a minor source for the insect invasions in China (9.1%), which predominantly originated from other parts of Asia (40.3%). These different patterns likely reflect the dissimilar trends of the trade in ornamental plants. Taxonomic and guild composition of non-native insects in both regions confirmed that ornamental trade of plants for planting including fruit trees played a larger role than timber and wood trade in shaping the non-native entomofaunas associated to woody plants. Hemiptera, and subsequently sap suckers, largely dominated the non-native entomofauna in both regions. However, there were striking differences in the range of hosts these species colonized. Although fruit trees, and especially Citrus, are the most important hosts in both regions, tropical trees including palms were also highly colonized in China whereas deciduous trees, shrubs and conifers were proportionally more affected in Europe. Quite a half of the non-native insect species did not switch from their original, non-native host to natives ones in Europe whereas only a minority of these insect invaders still sticked to their original, non-native host in China. It may be due to the more important presence in China of native woody plants taxonomically close to the original host.